Evaluación de la fitorremediación de suelos contaminados con petroleo mediano por medio del pasto megathyrsus maximus, el girasol heliantbus annuus L y el trigo triticum aestivum en el campo Velásquez de mansarovar energy ubicado en Puerto Boyacá (2021)
Currently one of the most important environmental problems is the contamination of the soil by hydrocarbon spills, which occur in exploitation, drilling, production, refining, transportation activities or by violent acts against the oil infrastructure by groups outside the law. To solve this problem, there are different conventional treatment methods to recover the ecosystem, such as the application of surfactants, chemicals and even combustion. However, this research evaluated a promising and little used technique in Colombia, such as phytoremediation.